Optimizing decentralized production-distribution planning problem in a multi-period supply chain network under uncertainty - Raheleh Nourifar; Iraj Mahdavi; Nezam Mahdavi-Amiri; Mohammad Mahdi Paydar (Journal of Industrial Engineering International, 2018)
Decentralized supply chain management is found to be significantly relevant in today's competitive markets. Production and distribution planning is posed as an important optimization problem in supply chain networks. Here, we propose a multi-period decentralized supply chain network model with uncertainty. The imprecision related to uncertain parameters like demand and price of the final product is appropriated with stochastic and fuzzy numbers. We provide mathematical formulation of the problem as a bi-level mixed integer linear programming model. Due to problem's convolution, a structure to solve is developed that incorporates a novel heuristic algorithm based on Kth-best algorithm, fuzzy approach and chance constraint approach. Ultimately, a numerical example is constructed and worked through to demonstrate applicability of the optimization model. A sensitivity analysis is also made.
Keywords: 650; Decentralized supply chain; Production-distribution planning problem; Bi-level approach; Network design